Investigation of the Reaction Pathways of Biomass‐Derived Oxygenate Conversion into Monoalcohols in Supercritical Methanol with CuMgAl‐Mixed‐Metal Oxide. Issue 23 (7th November 2018) - Galebach, Peter H.; Thompson, Sean; Wittrig, Ashley M.; Buchanan, J. Scott; Huber, George W.
Abstract: Reaction pathways for the conversion of cellulose into C2 –C6 monoalcohols by supercritical methanol depolymerization and hydrodeoxygenation (SCM‐DHDO) over a CuMgAl oxide catalyst have been elucidated using a range of model compounds. SCM‐DHDO of intermediate oxygenates including glycerol, methyl lactate, and 1, 2‐ethanediol produces similar products as those produced from the SCM‐DHDO of cellulose. The pathway to C2 –C6 monoalcohols occurs through rapid C−C coupling reactions between methanol and diols followed by C−C scission between vicinal alcohol groups to produce two monoalcohols. Methyl‐branched monoalcohols are produced through a methyl shift in a secondary diol followed by dehydration. Esters are produced by dehydrogenative coupling between an adsorbed methoxy and a primary alcohol. Both dehydrogenation to a ketone and esterification to a methyl ester are in equilibrium with the corresponding alcohol and were reversible. Dehydration of diols is the slowest observed reaction and not a main pathway to monoalcohols. SCM‐DHDO of glucose, dihydroxyacetone, and cellulose all produced similar high molecular weight species indicating that condensation of intermediates can produce undesired side products. Abstract : The scissions, the scissions : Cellulose is converted into alcohols over CuMgAlO x catalyst in supercritical methanol. The reaction proceeds through retroaldol condensation of cellulose to oxygenates, condensation with methanol, and C−C scission reactions to monoalcohols (see scheme).